Strategies of China and India in the Indo-Pacific region - E. S. Karsanova (Управление)
The article explores and assesses the strategic initiatives of China and India in the Indo-Pacific region, identifies new geopolitical problems and strategic dilemmas, and discusses emerging opportunities and options to address evolving threats and challenges. Special attention has been paid to the policies of China, whose geopolitical interest revolves around three maritime zones such as the South China Sea, the Indian Ocean and the Pacific Ocean. China has been generally successful in achieving its regional objectives, but it is precisely because of this that it faces growing challenges for itself since defensive security measures are interpreted by regional states as offensive, which in practice converts into a rather fragile “balance of threats.” India has focused on defending its territory with a strong network of allies, which represents an advantage for the country both commercially and militarily, as well as a crucial element in containing Chinese influence in the region. That said, India is not seeking to become a balancing force in the Indo-Pacific region, but is using the current tensions between the United States and China as a real chance to counter Chinese expansion. In the author’s opinion, the steady trend of military buildup (including in disputed territories), infrastructure network densification, and “special strategic and global partnerships” formation point to the strategic competition growth and increase the likelihood of confrontation escalation in the coming decades.